Perancangan E-Commerce Berbasis Web Pada PT. Touch Technology Indonesia - Saubani, Ahmad; Nainggolan, Esron Rikardo; Khasanah, Siti Nur (Program Studi Teknik Informatika Universitas Pamulang, 2019)
Sales in this case in the form of product sales is one of the important activities for the development of the company and is a very important aspect for the company. Problems a rising in the company regarding the promotion and sales, because it still uses manually, visit home for promotion and provide brochures on the road side, System design used with a waterfall methode, while the data collection techniques use research methods with observation, interviews, and library studies. And database application development tools use MySQL and PHP programming language by using Laravel framework. The purpose of this research is to design a sales system evenly and ease of transaction customers without having to come to physical stores directly. The result of this research is to provide an alternative sales and promotion. It is application created can create increase in company sales.